2011
DOI: 10.2337/db11-0203
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Bypass Surgery Enhances Glucagon-Like Peptide 1–Stimulated Postprandial Insulin Secretion in Humans

Abstract: OBJECTIVEGastric bypass (GB) surgery is associated with postprandial hyperinsulinemia, and this effect is accentuated in postsurgical patients who develop recurrent hypoglycemia. Plasma levels of the incretin glucagon-like peptide 1 (GLP-1) are dramatically increased after GB, suggesting that its action contributes to alteration in postprandial glucose regulation. The aim of this study was to establish the role of GLP-1 on insulin secretion in patients with GB.RESEARCH DESIGN AND METHODSTwelve asymptomatic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
267
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(301 citation statements)
references
References 31 publications
24
267
6
2
Order By: Relevance
“…Others (32) have reported that surgical restoration of gastric restriction to slow down the release of glucose into the intestine improved hypoglycaemia. However, in a recent study, the exaggerated effect of GLP1 on postprandial insulin secretion in surgical subjects was not significantly different from those with and without recurrent hypoglycaemia (14).…”
Section: Incretin Hormones and The Pancreatic Insular Axismentioning
confidence: 76%
See 1 more Smart Citation
“…Others (32) have reported that surgical restoration of gastric restriction to slow down the release of glucose into the intestine improved hypoglycaemia. However, in a recent study, the exaggerated effect of GLP1 on postprandial insulin secretion in surgical subjects was not significantly different from those with and without recurrent hypoglycaemia (14).…”
Section: Incretin Hormones and The Pancreatic Insular Axismentioning
confidence: 76%
“…The improvement in diabetes following GBS is thought to result from decreased insulin resistance associated with caloric restriction and weight loss and enhanced insulin secretion through an altered enteroinsular axis (12,13,14), and even possibly through the activation of dormant b-cells (15). Reports of PHH following GBS first appeared in 2004 (3,16).…”
Section: Discussionmentioning
confidence: 99%
“…This time lag was much more pronounced after RYGB. The later decrease in plasma glucose was partly due to decreasing oral glucose R a , but more importantly also to enhanced and prolonged glucose disappearance in response to hypersecretion of insulin, possibly due to exaggerated GLP-1 release [8,9]. As a consequence, the glucose concentration had already reached the basal level 2 h postprandially, followed by a brief period of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 98%
“…Using exendin(9-39), it has been shown that endogenous GLP-1 inhibits glucagon, stimulates insulin, and contributes to the incretin effect in both healthy subjects and patients with T2D (13)(14)(15). So far, studies employing the GLP-1R antagonist after RYGB revealed that GLP-1 contributed to an exaggerated insulin response after RYGB (16)(17)(18). b-Cell glucose sensitivity was doubled within 3 months after surgery, reversed by exendin(9-39) (17).…”
mentioning
confidence: 99%